Reduced temporal and spatial stability of neural activity patterns predict cognitive control deficits in children with ADHD - Gao, Zhiyao; Duberg, Katherine; Warren, Stacie L.; Zheng, Li; Hinshaw, Stephen P.; Menon, Vinod; Cai, Weidong (Nature communications, 2025)
This study investigates the neural underpinnings of cognitive control deficits in attention-deficit/hyperactivity disorder (ADHD), focusing on trial-level variability of neural coding. Using fMRI, we apply a computational approach to single-trial neural decoding on a cued stop-signal task, probing proactive and reactive control within the dual control model. Reactive control involves suppressing an automatic response when interference is detected, and proactive control involves implementing preparatory strategies based on prior information. In contrast to typically developing children (TD), children with ADHD show disrupted neural coding during both proactive and reactive control, characterized by increased temporal variability and diminished spatial stability in neural responses in salience and frontal-parietal network regions. This variability correlates with fluctuating task performance and ADHD symptoms. Additionally, children with ADHD exhibit more heterogeneous neural response patterns across individuals compared to TD children. Our findings underscore the significance of modeling trial-wise neural variability in understanding cognitive control deficits in ADHD. This study reveals heightened temporal variability and reduced spatial stability of task-evoked neural representations in children with ADHD, contributing to inefficient cognitive control and greater behavioral instability.